Layʻ tī Cha rā toʻ Bhu rāʺ krīʺ phre krāʺ toʻ mū ʼapʻ so Karacʻyo vāda khoʻ Buddhabhāsā nhaṅʻʹ Thāvara Brahmā kyamʻʺ - Ñāṇa, Ledi Cha rā toʻ, 1846 or 7-1923 or 4. (Sudhamma Cā puṃ nhipʻ tuikʻ, 1952)
Answers by a Buddhist monk to miscellaneous questions posed by some Christians.